Zinc-doped biphasic calcium phosphate nanopowders synthesized via sol-gel method - Gunawan, -; Sopyan, Iis; Suryanto, -; Naqshband, Abreeq (Scientific Publishers of India, 2014)
Zinc-doped biphasic calcium phosphate (BCP) powders have been synthesized via sol-gel method. The dopant concentration ions were adjusted at 1, 2, 3, 5, 10 and 15 mol%. The powders have been calcined at varying temperatures ranging from 500-900 °C and then characterized by XRD, FTIR, TG/DTA, TEM and FESEM data. X-ray diffraction patterns show that the phases present in Zn-doped BCP are hydroxyapatite, β-TCP and parascholzite. FTIR analysis reveal that the separation of three PO4 3- stretching peaks is obscure and OH bending peak at 630 cm-1 broaden with an increase in Zn concentration, whereas the PO4 3- band of TCP at 1085 cm-1 is sharper at higher calcination temperatures. Morphology analysis show that the size of agglomerates tends to increase with the increasing Zn concentration. These findings indicate that an increase in Zn level doped to the BCP affects the phase composition, crystallization and microstructure of the samples.